RESEARCH OF THE EFFICIENCY OF USING BLOCKCHAIN TECHNOLOGY IN GAMING APPLICATIONS - Калита, Надія; Лимар, Ліліана (SWorldJournal, 2023)
Blockchain is one of the modern technologies that is used in the development of game applications - mainly to create a game economy and describe the ownership of game items, which is due to the history of the creation of blockchain technology. One of the